Risk factors for mortality in patients with Stenotrophomonas maltophilia infection in Hatyai Hospital - Nitchot , Watjanarat; Arunyapongpaisan, Burin (Princess of Naradhiwas University Journal, 2023)
Stenotrophomonas maltophilia is a multidrug resistant bacterium that can cause nosocomial infection leading to high mortality rate. This study aimed to assess the risk factors for mortality and antibiotic use regarding S. maltophilia infection. A retrospective analytical study was performed by collecting patients with S. maltophilia infection between June 2015 and June 2018 from a hospital database. The SPSS Program reported correlation size of data with odds ratio and analyzed variable correlation using multivariate logistic regression. The data significantly differed with a p-value <0.05. Altogether, 404 patients with S. maltophilia infection were included; mean age 60.6 years and mostly males (67.8%). The most frequent infection types were respiratory tract, skin and soft tissue and urinary tract at 81.9, 5.7 and 4.5%, respectively. The susceptibility of microbes to trimethoprim /sulfamethoxazole, levofloxacin and sulbactam/cefoperazone were 90.6, 87.4 and 85.6%, respectively. The overall mortality rate was 19.9%. Based on univariate analysis, the variables significantly associated with mortality were heart disease (P=0.004), HIV positive (P=0.049), immunosuppressive therapy (P=0.014), indwelling catheter insertion (P=0.005), endotracheal intubation (P<0.001), central venous catheter insertion (P<0.001) and surgery (P=0.001). Based on multivariate analysis, the variables significantly associated with mortality were endotracheal intubation (P<0.001), central venous catheter insertion (P=0.002) and surgery (P<0.001). In conclusion, endotracheal intubation and central venous catheter insertion were significantly associated with mortality among patients with S. maltophilia infection. Microbes are still susceptible to trimethromprim/sulfamethoxazole which was the first line drug and to levofloxacin and sulbactam/cefoperazone as alternative agents.